Communicative competence of future teachers of elementary school as a psychological and pedagogical problem (Pedagogy of Higher and Secondary Education, 2012)
Kipichenko N. Communicative competence of future teachers of elementary school as a psychological and pedagogical problem.The article reviews the main approaches of domestic and foreign scientists to determine the nature and structure of communicative competence, the essence and meaning of «communicative competence of primary school teachers» defined structural components of communicative competence of primary school teacher.
Keywords: competence; communicative competence of primary school teachers; language competence; sociolinguistic competence